2018
DOI: 10.1515/med-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Is awareness enough to bring patients to colorectal screening?

Abstract: AbstractBackgroundThe aim of the study was to assess the awareness of colorectal cancer (CRC) patients about CRC screening methods and to investigate the relationship between awareness, socio-demographic characteristics and the stage in which patients with CRC are diagnosed.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, inadequate knowledge among medical staff may be one of barriers affecting colorectal cancer screening rates [ 13 ]. One of the Romanian study found that health professionals did not at all contribute to providing patients with information about screening methods in colorectal cancer [ 14 ]. Different types of media were the leading sources of information in that population followed by the interpersonal contacts (family and friends).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inadequate knowledge among medical staff may be one of barriers affecting colorectal cancer screening rates [ 13 ]. One of the Romanian study found that health professionals did not at all contribute to providing patients with information about screening methods in colorectal cancer [ 14 ]. Different types of media were the leading sources of information in that population followed by the interpersonal contacts (family and friends).…”
Section: Discussionmentioning
confidence: 99%